Effectiveness of Education Based on Neurosciences in Patients with Chronic Low Back Pain: Systematic Review with Meta-Analysis [Efectividad de la Educación Basada en Neurociencias en Pacientes Con Dolor Lumbar Crónico: Revisión Sistemática Con Metaanálisis] - Valdes-Orrego, I (Ediciones Doyma, S.L., 2018)
Background: Chronic low back pain syndrome (CLBPS) is a pathology characterised by functional impotence, pain, and psychological alterations. Design: A synthesis of evidence was made using a systematic review with a meta-analysis of clinical trials that have evaluated the effectiveness of education based on neurosciences (EBN) in patients with CLBPS. Objective: The aim of the article is to determine if there is scientific evidence to support the effectiveness of EBN in the improvement of pain and function of patients with CLBPS. Methods: Only randomised clinical trials (RCTs) were selected. The databases used were: Medline, Cochrane Central, Cinahl, Lilacs, SportDiscus, and PEDro. Results: A total of 13 articles were obtained that met the eligibility criteria, five of which made it possible to perform a quantitative analysis. The risk of bias was evaluated according to the Cochrane method. Conclusion: It is concluded that there is some evidence in favour of EBN in the improvement of pain intensity, functionality, and affective aspects of pain in patients with CLBPS, in the medium term. © 2018 Asociación Española de Fisioterapeutas